Undang Undang Adat : Tinjauan Pranata Hukum Adat Minangkabau dalam Teks Kuno - Fitri Nur Alifah (Protasis: Jurnal Bahasa, Sastra, Budaya, dan Pengajarannya, 2023)
Malay culture that developed in the Nusantara provides an intellectual heritage in the form of ancient texts, one of which text of Undang Undang Adat (UUA). The UUA text is a text containing Minangkabau customary law. This text was written in 1858 by Datuk Raja Bandara using Arabic-Malay script. The aim of this research is to reveal Minangkabau customary law institutions in the UUA Text. The method used in this research is descriptive qualitative. Data obtained from the text will be analyzed and explained systematically. Based on reviewing the contents of the text, this research produces findings of customary legal institutions which include (1) cupak nan duo, namely cupak usali and cupak artificial, (2) four laws, namely the nagari law, law in nagari, law -luhak law, and nan twenty laws, (3) kato nan ampek namely kato pusako, kato mufakat, kato kudian bacari, kato dulu batapati, (4) judge's debt or obligation of the judge, and (5) sanctions for violations custom.